Implementing a rapid cascade training model to enhance laboratory response during the Sudan virus disease outbreak in Uganda, 2022 - Roggers Michael Eilu; Morgan Otita; Daniel Kiiza; Benson Musinguzi; Gerald Aluma; Ronald Ocatre; Claire Nankoma; Andrew Kwiringira; Paddy Mutungi Tukamuhebwa; Dathan Byonanebye; Maureen Kesande; Boneventure Brian Kawere; et al. (Journal of Interventional Epidemiology and Public Health, 2025)
Introduction: In September 2022, Uganda experienced an outbreak of Sudan Virus Disease. We describe the roll-out of a rapid cascade training model which was implemented to enhance the capacity of laboratory response teams in managing samples at both national and subnational levels. Method: A training package was developed, reviewed by laboratory pillar members and approved by the Ministry of Health. The laboratory pillar team facilitated a national training program for trainers from national and specialized referral laboratories. Officers trained at the national level then trained regional laboratory officers, who trained district-level trainers and personnel from health facilities. The mean pre-test and post-test scores were compared using the paired t-test to evaluate knowledge improvement among participants. The turnaround time for laboratory results before and after training was monitored using the national results dispatch system. Results: Within two weeks of the development of the training package, 89 national and 133 regional trainers were trained, alongside 685 district laboratory response teams, 60 hub riders and drivers, and 86 mortuary attendants. There was a marked improvement in post-test knowledge assessments versus pre-test scores at both national and sub-national levels, as well as across all targeted health worker cadres from 59% to 87% (p<0.001). The swift increase in the number of personnel available to collect and refer samples post-training contributed to a rise in the number of samples collected, from 315 in the initial two weeks of response prior to the training, to a cumulative total of 4,430 by the conclusion of the outbreak. Additionally, the turnaround time was reduced from 144 hours before training to 24 hours after training. Conclusion: Implementing rapid cascade training during an outbreak response is both practical and advantageous. It boosts laboratory personnel’s confidence in handling high-risk pathogen samples and enhances sample quality. The quick increase in trained laboratory staff in the intervention areas led to more personnel available for quality sample management, reduced fatigue among the initially small team, and consequently, a shorter turnaround time.